Role of Low-Dose Theophylline on Functional Improvement in Patients of Moderately Severe Chronic Obstructive Pulmonary Disease - Farooq, Muhammad Umer; Saeed, Iqra; Ul Hassan, Saif; Zaman, Sajid; Shah, Maham; Hussain, Sajid (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the frequency of functional improvement in patients of COPD receiving low-dose Theophylline.Study Design: Case series.Place and Duration of Study: Junior Leaders Academy Hospital, Shinkiari, Mansehra Pakistan, from Feb to Jul 2021.Methodology: Patients with a previous chronic obstructive pulmonary disease diagnosis with Global Initiative for Chronic Obstructive Lung Disease stage 2/3, taking long-acting muscarinic antagonists were included in the study. In addition, patients were prescribed sustained released Theophylline 150mg daily and other previously prescribed medications. The assessment was done before the start of the study with the COPD assessment tool (CAT) questionnaire and followed up with monthly CAT scores.Results: There were 78(81.25%) males and 18 females (18.75%). An increase in the CAT score of more than 2 was a significant improvement. The most common baseline CAT score was 34.26±2.67 (range 0-40 with a higher score denoting a more severe impact of COPD) with a frequency of 16(16.7%). The least commonly occurring CAT score at baseline was 39 and 40(2.1%).The improvement in the CAT score was observed in 42 patients.Conclusion: Early and prompt treatment for COPD will reduce the outcomes by decreasing hospital admissions and better quality of life. This study reaffirms low-dose Theophylline as an add-on therapy in patients with moderately severe COPD.